Emerging roles of interferon-stimulated gene-15 in age-related telomere attrition, the DNA damage response, and cardiovascular disease - González-Amor, María; Dorado, Beatriz; Andrés, Vicente (Frontiers in Cell and Developmental Biology, 2023)
Population aging and age-related cardiovascular disease (CVD) are becoming increasingly prevalent worldwide, generating a huge medical and socioeconomic burden. The complex regulation of aging and CVD and the interaction between these processes are crucially dependent on cellular stress responses. Interferon-stimulated gene-15 (ISG15) encodes a ubiquitin-like protein expressed in many vertebrate cell types that can be found both free and conjugated to lysine residues of target proteins via a post-translational process termed ISGylation. Deconjugation of ISG15 (deISGylation) is catalyzed by the ubiquitin-specific peptidase 18 (USP18). The ISG15 pathway has mostly been studied in the context of viral and bacterial infections, where it plays a protective role, and as a tumor suppressor. This minireview summarizes current knowledge on the role of ISG15 in age-related telomere shortening, genomic instability, and DNA damage accumulation, as well as in hypertension, diabetes, and obesity, major CVD risk factors prevalent in the elderly population.